Goddess Rice Center growth plan - Go, John Christopher N. (Animo Repository, 2022)
The chosen business for the family growth plan is Goddess Rice Center, a merchandising and retailing business focused on rice selling. The business falls under a sole proprietorship and was started in 2009 by its owner and operator Ms. Giok Yong Tan. One of the reasons as to why the business was started was primarily because the family members of the owner were all business owners operating in the agricultural industry, with some having its own milling and importation branches, that also became the suppliers of Goddess Rice Center. The business has come a long way ever since its birth in 2009. At present, the business has already expanded its operations and reached into different locations. Most of the sales of the business come from its sales to canteens, rice dealers, distributors, restaurants, markets, and individual consumers which have all become regular long-time customers already, proving the strong success of the business. One of the largest producers, importer, and exporter of agricultural products in the Philippines, especially of rice due to the massive land area the country boasts that is the main foundation of its strong agricultural landscape. Some of its main rival countries are Japan, Indonesia, Vietnam, and other ASEAN countries that are large importers and exporters of crops. In the specific context of the Philippines, rice is considered a staple in every Filipino household that has already become a part of Filipino food culture. Filipinos are also reported to be one of the biggest consumers of rice across the entire world with a Filipino individual consuming an average of almost 120 kilograms of rice per year, compared to Americans that only average 12 kilograms in the exact time period. Rice is also the main source of carbohydrates for Filipinos compared to Europeans who have pasta and bread as their own. Due to the substantial demand for rice and other agricultural products, the agricultural sector is one of the most extensive contributors to the overall economic growth of the Philippines with an estimated 7-9% of the growth domestic product (GDP) between years 2017 and 2019, in which a big portion of the growth emerging from the continuous development in the rice and retail industry. Researchers also mention that rice accounts for more than 20% of the growth value added (GVA), also one indicator of economic growth and health. In line with this finding, the agricultural sector accounts for almost a quarter of the entire labor force of the country as mentioned in a report by the World Bank Collection of Development Indicators last 2020 (as cited in Trading Economics). Despite the global pandemic, the store has consistently performed well since the products offered by Goddess Rice Center are necessary to all Filipinos, namely rice. Furthermore, the researchers have developed a set of diverse strategies focusing on various parts of the firm, such as market development strategies, Market Penetration Strategies, Product Development Strategies, and Management Development Strategies through a series of practicums that would assist the organization improve and remain competitive in the industry. To ensure progressive business growth through expanded operations, and to prolong the lifespan and sustainability of the business, the group had planned different activities for Goddess Rice Center. The activities are divided into three segments that comprises two activities specifically designed to work and complement one another to achieve better effectivity and efficiency that will be measured through the sales and finances of the business. The first set of activities are Establishment of a Digital Inventory System and Integrating a point of sale system (POS). These activities would be done from October to February 2022. The second of activities are Tapping into Electronic Commerce and Formation of Partnership between Fast Food Restaurants. These activities would be done from February to May 2022. And for the last of activities: New store branch and franchise. This two activities would be done from June to September 2022